Risk Factors for Heart Failure in Patients With Chronic Kidney Disease: The CRIC (Chronic Renal Insufficiency Cohort) Study. Issue 5 (17th May 2017) - He, Jiang; Shlipak, Michael; Anderson, Amanda; Roy, Jason A.; Feldman, Harold I.; Kallem, Radhakrishna Reddy; Kanthety, Radhika; Kusek, John W.; Ojo, Akinlolu; Rahman, Mahboob; Ricardo, Ana C.; Soliman, Elsayed Z.; et al.
Abstract : Background: Heart failure is common in patients with chronic kidney disease. We studied risk factors for incident heart failure among 3557 participants in the CRIC (Chronic Renal Insufficiency Cohort) Study. Methods and Results: Kidney function was assessed by estimated glomerular filtration rate (eGFR) using serum creatinine, cystatin C, or both, and 24‐hour urine albumin excretion. During an average of 6.3 years of follow‐up, 452 participants developed incident heart failure. After adjustment for age, sex, race, and clinical site, hazard ratio (95% CI) for heart failure associated with 1 SD lower creatinine‐based eGFR was 1.67 (1.49, 1.89), 1 SD lower cystatin C‐based‐eGFR was 2.43 (2.10, 2.80), and 1 SD higher log‐albuminuria was 1.65 (1.53, 1.78), all P <0.001. When all 3 kidney function measures were simultaneously included in the model, lower cystatin C‐based eGFR and higher log‐albuminuria remained significantly and directly associated with incidence of heart failure. After adjusting for eGFR, albuminuria, and other traditional cardiovascular risk factors, anemia (1.37, 95% CI 1.09, 1.72, P =0.006), insulin resistance (1.16, 95% CI 1.04, 1.28, P =0.006), hemoglobin A1c (1.27, 95% CI 1.14, 1.41, P <0.001), interleukin‐6 (1.15, 95% CI 1.05, 1.25, P =0.002), and tumor necrosis factor‐α (1.10, 95% CI 1.00, 1.21, P =0.05) were all significantly and directly associated with incidence of heart failure. Conclusions: Our study indicates that cystatin C‐based eGFR and albuminuria are better predictors for risk of heart failure compared to creatinine‐based eGFR. Furthermore, anemia, insulin resistance, inflammation, and poor glycemic control are independent risk factors for the development of heart failure among patients with chronic kidney disease.